Implementasi Pembelajaran berbasis e-Learning berbantuan aplikasi open source Jamovi pada Mata Kuliah Statistika - I Made Dedy Setiawan (UNIB Press, 2026)
Statistics, as one of the courses in the Informatics study program at INSTIKI, uses e-learning in its learning process. The role of statistics is crucial in the field of informatics because statistics is one of the important foundations in the field of technology, especially data-based decision making. In reality, statistics learning has not been facilitated using relevant learning media in the current digital era. Therefore, efforts are needed to utilize technology, one of which is by utilizing open source applications. The purpose of this study was to determine the effect of implementing e-learning-based learning assisted by the open source application jamovi in ​​statistics courses. This study is a quasi-experimental study with a posttest-only control group design. Samples were taken purposively and obtained 56 students divided into the experimental group and the control group. Data were collected using a statistics learning outcome test and analyzed using descriptive statistics, analysis prerequisite tests, and hypothesis testing. The results showed that there was a significant difference in the average score of the statistics learning outcomes of the experimental group and the average score of the statistics learning outcomes of the control group with a significance of less than 5%. Thus, there is an effect of the treatment on the dependent variable.